Chances, challenges and outcomes of patients with complex bilobar colorectal liver metastases approached by a combined multimodal therapy with liver resection and local ablative therapy. Issue 7 (8th March 2021) - Drefs, Moritz; Schoenberg, Markus B.; Schiergens, Tobias S.; Albertsmeier, Markus; Andrassy, Joachim; Angele, Martin K.; Westphalen, Christoph B.; Seidensticker, Max; Werner, Jens; Guba, Markus O.
Abstract: Background and Objectives: In treatment of colorectal liver metastases (CRC‐LM), liver surgery combined with systemic therapies and local ablation (LAT) allows improved survival. This study aims at the outcomes of patients with complex bilobar CRC‐LM who were intended to undergo multimodal therapy with liver resection and LAT. Methods: Forty‐three CRC‐LM patients with recommendation for multimodal treament were extracted from 5878 tumor board decisions between 2014 and 2017. Outcome variables included patient survival, as well as completion of hepatic clearance. Prognostic factors were identified by correlation and a Cox proportional hazards model. Results: Out of 43 patients only 23 achieved complete clearance of CRC‐LM. One‐ and 3‐year overall survival of patients with cleared liver disease was 100% and 91.7%, respectively, as compared to 83.8% and 12.1%. Incomplete hepatic clearance was the strongest independent risk factor for overall survival (hazards ratio [HR], 5.86; p = .009). Risk factors for incomplete clearance were higher age ( r = .34; p = .026), comorbidities ( r = .40; p = .008), major complications ( r = .34; p = .024), and prolonged intensive care unit stay ( r = .41; p = .017). Conclusion: Completion of hepatic clearance is crucial to achieve long‐term survival in patients with complex bilobar CRC‐LM. Careful patient selection and treatment planning should avoid treatment failure before completing the intended therapy plan when multimodal treatments are planned.